Paradojas de las educaciones populares y sus actores en tiempos de gobiernos progresistas y coronavirus - Mejia, Marco Raul (Cadernos CIMEAC, 2020)
O texto analisa impasses e perspectivas para a educação a partir dos governos progressistas latino-americanos do início dos anos 2000, bem como os significados da pandemia de covid-19 para o campo. Posicionando os movimentos de educação popular no contexto do Sul global, o autor defende uma proposta aberta à pluralidade e à participação política dos setores populares.Palavras-chave: Educação popular; Sul global; Crise; Mobilização. ABSTRACT: The article analyzes impasses and perspectives for popular education within the Latin American progressive governments of the early 2000s, as well as the meanings of the COVID-19 pandemic for the field of popular education. By placing popular education movements in the context of the global South, the author defends a proposal open to plurality and political participation by popular sectors.Keywords: Popular education; Global South; Crisis; Mobilization.